Answer:
It is not a solution
Step-by-step explanation:
Plug the point into the equations and check to see if they are true
y=3x - 3
3 = 3(6) -3
3 = 18-3
3 = 15
False
We do not need to check the other equation since this is false
We have that
<span>If (5x-4+13x=5) --------------> then x=1/2
Step 1
</span>let's substitute the value of x = (1/2) in the expression [5x-4+13x] and verify its result
5*(1/2)-4+13*(1/2)
(5/2)-4+(13/2)
(5-4*2+13)/2----------> (5-8+13)/2=10/2=5
then
5=5-----------> <span>the value of x = (1/2) satisfies equality</span>
Answer:
2
Step-by-step explanation:
a = 1/2ab
~Divide 1/2a to both sides
2 = b
Best of Luck!
Answer:
x = 7
Step-by-step explanation:
Rule: an even number of - signs written one after another produces a plus number.
So - - 3 = 3
The rule also lets you do something strange like
- - - - 4 = 4 but you hardly ever see this.
Rule: an odd number of minus signs produces a minus number.
x + 3 = 10 Subtract 3 from both sides.
x + 3 - 3 = 10 - 3
x = 7
Answer:
15 is 30% of 50
Step-by-step explanation:
We have, 30% × x = 15
Multiplying both sides by 100 and dividing both sides by 30,
we have x = 15 × 100/30
x = 50
If you are using a calculator, simply enter 15×100÷30, which will give you the answer.